Ã˜ÂªÃ˜Â·Ã™Ë†Ã™Å Ã˜Â± Ã™Ë†Ã˜Â³Ã™Å Ã™â€žÃ˜Â© Ã˜ÂªÃ˜Â¹Ã™â€žÃ™Å Ã™â€¦ Ã™â€¦Ã™â€¡Ã˜Â§Ã˜Â±Ã˜Â© Ã˜Â§Ã™â€žÃ˜Â§Ã˜Â³Ã˜ÂªÃ™â€¦Ã˜Â§Ã˜Â¹ Ã˜Â¨Ã˜Â¨Ã˜Â±Ã™â€ Ã˜Â§Ã™â€¦Ã˜Â¬ Ã˜Â£Ã™Ë†Ã˜Â¯Ã˜Â§Ã˜Â³Ã™Å Ã˜ÂªÃ™Å (Audacity) Ã™ÂÃ™Å Ã˜Â§Ã™â€žÃ™â€¦Ã˜Â¯Ã˜Â±Ã˜Â³Ã˜Â© Ã˜Â§Ã™â€žÃ™â€¦Ã˜ÂªÃ™Ë†Ã˜Â³Ã˜Â·Ã˜Â© Ã™â€¦Ã˜Â¹Ã™â€¡Ã˜Â¯ Ã™â€ Ã™Ë†Ã˜Â± Ã˜Â§Ã™â€žÃ˜Â¥Ã˜ÂÃ˜Â³Ã˜Â§Ã™â€ Ã˜Â§Ã™â€žÃ™â€¦Ã˜Â¹Ã˜Â§Ã˜ÂµÃ˜Â± Ã˜Â¨Ã˜Â§Ã™â€ Ã˜Â§Ã™â€¦Ã˜Â¨Ã™Ë†Ã™â€ Ã˜Â¬ Ã˜Â¨Ã˜Â³Ã™Ë†Ã™â€¦Ã˜Â·Ã˜Â±Ã˜Â© Ã˜Â§Ã™â€žÃ˜ÂºÃ˜Â±Ã˜Â¨Ã™Å Ã˜Â© - Jafar, Muslim; Aisyah, Devy; Amrina, Amrina (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2020)
This reseach aimed to develop Arabic listening learning media by using Audacity Programme for the students of Pondok Pesantren Modern Nurul Ihsan Panampung Sumatera Barat. The reseach used R & D method. While, development model used 4-D model : Define, Design, Develop without Disseminate. The result showed that the media of arabic listening which is developed by using audacity can be used properly for the students of Pondok Pesantren Modern Nurul Ihsan Panampung in West Sumatra. According to the expert judgement, the develop media is valid, while the average score is 84.68